Парадигма у світоглядно-культуротворчому аспекті - Федь, В. (Схід, 2011)
У статті здійснено теоретичне осмислення світоглядних парадигм у формуванні, становленні та розвитку культуротворчого буття. Світоглядні парадигми є стимуляторами соціокультурної діяльності, із якою нерозривно пов'язані в культуротворчому бутті. Універсальні парадигми (язичницька, християнська та наукова) мають світоглядні (ідеал та ін.)
та діяльнісні (духовні та ін.) проекції. The thesis deals with theoretical consideration of the ideological paradigms in the formation and development of the cultural-creative being. Ideological paradigms are considered to be stimulators of social-cultural activity with
which they are inseparably interrelated in the cultural-creative being. There is provided a table of significats of the cultural creative being; the structural elements include key paradigms (pagan, Christian and scientific) which have ideological (ideal and others) and activity (spiritual and others) projections.